Effects of neuromuscular electrical stimulation on exercise capacity and quality of life in COPD patients: a systematic review and meta-analysis. Issue 5 (27th May 2020) - Wu, Xu; Hu, Xianglin; Hu, Weiping; Xiang, Guiling; Li, Shanqun
Abstract: Neuromuscular electrical stimulation (NMES) has been shown to produce benefits in the muscle function of chronic obstructive pulmonary disease (COPD) patients. The definite effectiveness of NMES, applied in isolation or concurrently with conventional pulmonary rehabilitation (PR) or exercise training, remains unclear. This review was to determine the effects of NMES on exercise capacity, functional performance, symptoms, and health-related quality of life (HRQoL) in COPD patients. Electronic databases (PubMed, Embase, Web of Science, the Cochrane Library) were searched for relevant randomized controlled trials (RCTs). Two investigators independently screened the eligible studies up to February 2020 that used NMES as the intervention group. The outcome measures were 6-min walking distance (6MWD), peak rate of oxygen uptake (VO2 peak), St George's Respiratory Questionnaire (SGRQ), and symptoms of dyspnoea and fatigue. Data were extracted using a predefined table and papers were appraised using Downs and Black tool. We analyzed 13 RCTs with 447 COPD patients. In the analysis of 6MWD, pooled estimates showed a significant increase in the NMES group, compared with the control group (mean difference (MD) = 27.05, 95% confidence interval (CI): 8.46–45.63, P <0.001). There were also improvements in symptoms of dyspnea or leg fatigue, and reduction in London Chest Activity of Daily Living (LCADL) scores. No statistically significant difference was observed in VO2 peak, peak power, and SGRQ. NMES could improve exercise capacity and reduce perceived sensation of dyspnea during exercise in patients with COPD, but not to be recommended as an effective alternative training modality in the rehabilitation of stable COPD patients.